KONSEP DIRI PARA PEMAIN GAME ONLINE MOBILE LEGEND: BANG BANG DI INDONESIA - Albert (2024)
This research examines individual interactions as mobile legend online game players who play in the realm of cyberspace. Individual interactions in the game contribute to constructing self-concept. The researcher's focus is on the shift from personal computer online games to smartphones. In games mediated by smartphones, there is flexibility in playing. The researcher's assumption is that frequent playing intensity will facilitate value transactions that are easily absorbed by individuals. Therefore, the researcher aims to analyze the self-concept of mobile legend online game players through self-concept theory to get an idea of how the self-concept of mobile legend online game players is from the interactions that occur and explain through mead ("I" and "Me" self-concept). This research has results that are based on self-concept theory which is divided into the I element and the Me element in mobile legend players. It was found that aggressive communication occurred in both elements of the players' self-concept but had different meanings in each element. "I" in the informant can be seen how aggressive communication is used as a form of self-expression to express feelings of irritation. Meanwhile, in the "Me", informants are more careful and use aggressive communication as a form of joking or friendship between friends.